Memorial acadêmico: trajetória escolar, acadêmica e profissional - SILVA, Andrya Karolina dos Santos (2022)
This academic Memorial is an autobiographical narrative, with results of surveys of my trajectory through Kindergarten, Elementary School, and Academic Education, reporting the experiences acquired over these years, considering that the facts presented deal with memories of this path taken and the main collaborations for my personal development. It aims to highlight the differences between the adaptations in rural and urban schools and present the perceptions in higher education, and the methodology applied in this study are memories regarding the educational trajectory presented by reports and authorial photographs, where the perception of teaching methods are visualized as a result and its positive and negative character is concluded in the student's life depending on its application or absence.